Cryptococcus neoformans var. neoformans (Serotype D) Strains Are More Susceptible to Heat than C. neoformans var. grubii (Serotype A) Strains - Martinez, Luis. R (American Society for Microbiology, 2001)
Cryptococcus neoformans var. neoformans (serotype D) and C. neoformans var. grubii (serotype A) differ in geographic prevalence and dermatotropism, with C. neoformans var. neoformans strains being more prevalent among isolates from temperate countries as well as from skin infections. Analysis of 19 strains from each serotype revealed wide variation in thermal susceptibility, with C. neoformans var. neoformans strains being more susceptible, on average, to heat killing. The results suggest a consistent explanation for the geographic differences between serotype A and D strains and for the dermatotropism of serotype D strains.